Hubungan Tingkat Pengetahuan Pasien dengan Perilaku Penggunaan Antibiotik di Klinik X Tahun 2025 : The Relationship Between Patients' Knowledge Level and Antibiotic Use Behavior at Primary Clinic X in 2025 - Siti Hodijah; Julia Totong; Dian Fitri Chairunnisa (UIMA Press, 2026)
Inappropriate use of antibiotics remains a global health problem because it can contribute to antibiotic resistance. Patients' level of knowledge is one of the factors associated with antibiotic use behavior. This study aimed to determine the relationship between patients' level of knowledge and antibiotic use behavior at Azka Zayyan Primary Clinic, Cianjur, during the period of June-August 2025. This study employed a quantitative analytical design with a cross-sectional approach. A total of 98 respondents were selected using a purposive sampling technique. Data were collected using a validated and reliable questionnaire. Data were analyzed using univariate and bivariate analyses with the Chi-Square test. The results showed that the majority of respondents had a moderate level of knowledge (55.1%), while most demonstrated poor antibiotic use behavior (56.1%). The Chi-Square analysis showed a p-value of <0.001 (p<0.05), indicating a significant relationship between patients' level of knowledge and antibiotic use behavior at Azka Zayyan Primary Clinic, Cianjur, during the period of June-August 2025.